On a nonlinear compactness lemma in Lp(0,T;B) - Emmanuel Maitre (International Journal of Mathematics and Mathematical Sciences)
We consider a nonlinear counterpart of a compactness lemma of Simon (1987), which arises naturally in the study of doubly nonlinear equations of elliptic-parabolic type. This paper was motivated by previous results of Simon (1987), recently sharpened by Amann (2000), in the linear setting, and by a nonlinear compactness argument of Alt and Luckhaus (1983).